2005
DOI: 10.1007/s00359-005-0053-x
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-rate recognition in an insect: evidence of a role for oscillatory neurons

Abstract: Various mechanisms have been proposed as the neural basis for pulse-rate recognition in insects and anurans, including models employing high- and low-pass filters, autocorrelation, and neural resonance. We used the katydid Tettigonia cantans to test these models by measuring female responsiveness on a walking compensator to stimuli varying in temporal pattern. Each model predicts secondary responses to certain stimuli other than the standard conspecific pulse rate. Females responded strongly to stimuli with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(51 citation statements)
references
References 35 publications
1
50
0
Order By: Relevance
“…1 and 2 we show that this simple model reproduces all the ''resonant'' properties of the bush cricket behaviour described in Bush and Schul (2006). Pulses of a constant duration (18 ms) played at frequencies from 8 to 67 Hz, produce the expected peak at 25 Hz, a second peak of half the size at 12.5 Hz, and a smaller increase at 8 Hz.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…1 and 2 we show that this simple model reproduces all the ''resonant'' properties of the bush cricket behaviour described in Bush and Schul (2006). Pulses of a constant duration (18 ms) played at frequencies from 8 to 67 Hz, produce the expected peak at 25 Hz, a second peak of half the size at 12.5 Hz, and a smaller increase at 8 Hz.…”
Section: Resultssupporting
confidence: 56%
“…However, the mechanism by which this recognition occurs is still a matter of debate (Hennig et al 2004). Behavioural experiments on the bushcricket Tettigonia cantans (Bush and Schul 2006) compared three alternative explanations for the female's band-pass preference for the pulse rate in male song: a circuit involving separate high-pass and low-pass filters; autocorrelation; and resonance. A stronger response to songs at integer fractions of the preferred frequency, and to other nonnatural songs that reinforce that rhythm, suggested that resonance is the best explanation.…”
Section: Introductionmentioning
confidence: 99%
“…Our recordings did not provide evidence for resonance in the auditory network as stimulation with calling song patterns did not lead to ongoing oscillations of the membrane potential of any of the neurons recorded. Furthermore, neither our behavioral data nor the response functions of our neurons revealed a secondary peak at one-half of the optimal pulse period as suggested by Bush and Schul (2006). Only the membrane potential of B-LC3 in some preparations transiently oscillated at ϳ34 Hz when stimulated with a constant tone of 160 ms (Fig.…”
Section: Structure Of Local Auditory Neurons Within the Brainmentioning
confidence: 52%
“…Evidence from Bush and Schul (2006) indicated that pattern selectivity may result from intrinsic membrane potential oscillations of auditory neurons resonating with the frequency of the species-specific pulse pattern. Our recordings did not provide evidence for resonance in the auditory network as stimulation with calling song patterns did not lead to ongoing oscillations of the membrane potential of any of the neurons recorded.…”
Section: Structure Of Local Auditory Neurons Within the Brainmentioning
confidence: 99%
See 1 more Smart Citation